2019
DOI: 10.1186/s12903-019-0810-9
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro evaluation of marginal fit zirconia crowns fabricated by a CAD-CAM dental laboratory and a milling center

Abstract: Background Marginal fit is critical for the success and longevity of a dental restoration. Zirconia crowns can be fabricated either chair-side, in a dental laboratory or in a milling center; each can give different marginal fits results. However, discussion of the marginal fit of zirconia crowns when different fabrication methods are compared is lacking in the literature. Purpose To compare the marginal discrepancy (MD) and absolute marginal discrepancy (AMD) of compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
2
17
0
4
Order By: Relevance
“…These results are comparable to this study's CEREC data, considering the difference between the marginal gap and AMD. However, other studies measured AMD with CEREC systems and obtained lower values, between 53 and 94 μm [19,22,53]. The lower values of these studies may come from ideal in vitro conditions obtained by scanning a single typodont tooth instead of a full dentate arch dentate.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These results are comparable to this study's CEREC data, considering the difference between the marginal gap and AMD. However, other studies measured AMD with CEREC systems and obtained lower values, between 53 and 94 μm [19,22,53]. The lower values of these studies may come from ideal in vitro conditions obtained by scanning a single typodont tooth instead of a full dentate arch dentate.…”
Section: Discussionmentioning
confidence: 94%
“…This means that AMD is higher than or in an ideal condition perhaps equal to the marginal gap. In studies measuring both parameters, the AMD was found to be 30-118% greater than the marginal gap [52][53][54]. Literature regarding marginal fit with chairside systems is available for CEREC, but most of them scanned typodont specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In this case prospective clinical study no chipping nor delamination of ceramic veneering were observed in 5 years. This good result achieved thanks to the marginal fit, which is critical for the success and longevity of a dental restoration [26]. The protocol adopted in this clinical trial leads to a substantial and advantageous reduction in costs and treatment times; it is supported by a high, long-term prognosis that, according to the studies carried out, ranges from 92 to 100% [19][20][21].…”
Section: Discussionmentioning
confidence: 96%
“…This can result in the fabrication of an incongruous prosthetic restoration [10,11]. An incongruous restoration, which presents non-optimal adaptation (for example, horizontal, vertical, or absolute marginal discrepancies), can produce a series of negative effects, such as greater accumulation or retention of plaque and therefore gingival inflammation (gingivitis) that can subsequently develop into periodontal pocket formation [17,18]; in addition, in the long term, complications such as secondary caries [19] and, in some susceptible biotypes, recessions can occur [20]. For all these reasons, the precision of a restoration does not exclusively represent the search for an optimal transition between the natural element and the prosthesis, but it is key to the longevity (or survival) of the restoration itself [2,11,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…An incongruous restoration, which presents non-optimal adaptation (for example, horizontal, vertical, or absolute marginal discrepancies), can produce a series of negative effects, such as greater accumulation or retention of plaque and therefore gingival inflammation (gingivitis) that can subsequently develop into periodontal pocket formation [17,18]; in addition, in the long term, complications such as secondary caries [19] and, in some susceptible biotypes, recessions can occur [20]. For all these reasons, the precision of a restoration does not exclusively represent the search for an optimal transition between the natural element and the prosthesis, but it is key to the longevity (or survival) of the restoration itself [2,11,[17][18][19][20]. To date, numerous techniques have been proposed for the correct scanning and visualization of the margins of prosthetic preparations on natural teeth, including traditional techniques used also with conventional impressions with polyethers/polyvinylsiloxane, such as placement of one or two gingival retraction cords [21,22], the use of retraction pastes [23], gels [24] or strips [25], and the use of a laser [26].…”
Section: Introductionmentioning
confidence: 99%